Prosocial Consequences of Interpersonal Synchrony: A Meta-Analysis - Rennung, Miriam (Z Psychol, 2016)
Abstract. The capacity to establish interpersonal synchrony is fundamental to human beings because it constitutes the basis for social connection and understanding. Interpersonal synchrony refers to instances when the movements or sensations of two or more people overlap in time and form. Recently, the causal influence of interpersonal synchrony on prosociality has been established through experiments. The current meta-analysis is the first to synthesize these isolated and sometimes contradictory experiments. We meta-analyzed 60 published and unpublished experiments that compared an interpersonal synchrony condition with at least one control condition. The results reveal a medium effect of interpersonal synchrony on prosociality with regard to both attitudes and behaviors. Furthermore, experimenter effects and intentionality moderate these effects. We discuss the strengths and limitations of our analysis, as well as its practical implications, and we suggest avenues for future research.